Pengaruh Metode Inkuiri Terhadap Keaktifan Belajar Dan Keterampilan Menyimpulkan Pada Mata Pelajaran Biologi Kelas X MAN 1 Kabupaten Lombok Barat - Risa Umami; Bunga Adeliana Lestari; Nurfadila Arifin; Aulia Zulfaeda (Otus Edu Journal Prodi Tadris IPA Biologi UIN Mataram, 2023)
This research aims to determine the effect of the inquiry method on active learning and concluding skills in the biology subject class X MAN 1 of West Lombok on ecosystem material. This research uses a quantitative approach with a quasi experimental type of research. The population in this study were students of X MAN 1 West Lombok. Sampling was taken using a saturated sampling technique. The samples for this research were students in classes X MIPA 1 and X MIPA 2. The research design used a nonequivalent control group design. This research instrument is in the form of observations and test questions. Research data analysis used statistical tests, namely the t-test using SPSS 22. The research results showed that there was an influence of the inquiry method on learning activeness (P<0.05) and concluding skills (P<0.05). So, this method is effectively implemented in learning to maximize mastery of the material that has been covered by the teacher.